Role of fluoroethyl tyrosine positron emission tomography-computed tomography scan in differentiating ewing's sarcoma from osteomyelitis - Aggarwal, Hitesh; D'souza, Maria; Panwar, Puja; Jyotsna, Neeru; Alvi, Tauheed; Solanki, Yachna; Kumar, Tarakant; Sharma, Rajnish (World Journal of Nuclear Medicine, 2019)
Ewing's sarcoma is a kind of undifferentiated reticulocytic sarcoma, which was first reported in 1921 by James Ewing. It is difficult to differentiate Ewing's sarcoma from osteomyelitis on computed tomography (CT) and X-ray and hence cytological confirmation is needed. Fluorodeoxy glucose being a nonspecific tracer cannot differentiate between malignant and inflammatory lesions. However, it is found that Ewing's sarcoma has increased LAT1 transporter expression at the cell surface. This property has been utilized to specifically target the tumor cells and differentiate them from inflammatory lesions. 18F-fluoroethyl tyrosine (FET) is a radiotracer which shows increased uptake in tumors having LAT1 expression and no uptake in inflammatory lesions. Thus, FET positron emission tomography-computed tomography can serve as a useful tool in diagnosing recurrence or residual Ewing's sarcoma from infective pathology. Besides, it is also helpful in monitoring response to therapy.
Keywords: Ewing's sarcoma; flouro-ethyl tyrosine; osteomyelitis